(3CfXeI GdJcGdja dCZQGV bjGS JcdaI GdEfJGL hGdNOeGJ aj HjFI GdCYeGd GdMOjKIs - (3UdGM GdOjf YHO GdefYe(B, (3eHGQcs ((3GdBScfOQjI(B:s (3OGQ GdeWHhYGJ GdLGeYjI(B,s, 2008)
(3NUGFU ELQGAGJ heMOOGJ JWHjb CfXeI JcGdja GdeQGMd,ELQGAGJ CfXeI JcGdja GdeQGMd aj MGdI EfJXGe EVGaI YfGUQ GdJcGdja,ELQGAGJ CfXeI JcGdja GdeQGMd aj MGdI YOe GfJXGe EVGaI YfGUQ GdJcGdja,ELQGAGJ CfXeI JcGdja GdeQGMd aj Xd eSehMGJ hNSGFQ GdJTZjd hJYOO GdefJLGJ,fXe JcGdja eJNUUI,fXGe GdJcGdja aj efTBJ GdEfJGL GdeJUd,fXGe JcGdja GdYbhO,fXGe JcGdja GdNOeGJ,fXGe JcGdja GdYedjGJ,fXGe GdGfJGL GdahQj hfXGe GdJOab GdYcSjs
Keywords: (3GdJcGdjas